CHARACTERIZATION OF THE ESSENCE OF THE HUMAN PHYSICAL CAPITAL CONCEPT IN RELATION TO THE FITNESS INDUSTRY - Cuprika, Aleksandra; Fernate, Andra; Cupriks, Leonids (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
A large part of the society perceives the body as a fundamental tool to advance in social life, as a capital in labour relations and in sexual relations as well. The possibility to transform one’s own physical capital into economic, social or cultural capital, which is an opportunity a person receives through carrying out physical activity, is also a value in the field of fitness which is an industry that is worth billions. That is why the aim of this study was to investigate in-depth characterization of the nature of the physical capital concept, linking it to the field of fitness. The study is based on 48 literature sources and scientific articles, 2 of which are in Latvian, 5 in Russian and 41 – in English. The essence of the content of the physical capital concept has been investigated and the connections of notions in different theoretical contexts has been evaluated, starting from the beginning of the physical capital concept. The definitions were grouped in a broader and narrower scope. In the narrower sense, physical capital is a person’s skills and abilities – innate or acquired over time –, which help to perform a specific physical work, move, strengthen or improve physical health and capacity for work. In the broader sense – as values and investments in the body, building of a body in society. In the broader sense of physical capital, the main goal is its transformation into other forms of capital in order to obtain additional benefits or a new status in the society.